PENANGKARAN PADI DALAM UPAYA PEMENUHAN BENIH MANDIRI PADA KELOMPOK TANI AIR SARASAH DI NAGARI SUNGAI BATANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Irfan Suliansyah; Fitri Ekawati; Doni Hariandi; Obel Obel; Nugraha Ramadhan; Rachmad Hersi Martinsyah; Winda Purnama Sari; Sanna Paija Hasibuan (Jurnal Hilirisasi IPTEKS, 2020)
One of the factors causing the low productivity of rice in West Sumatra Province is quality seeds, which are still very low. Also, many rice varieties currently used have a low resistance to pests and diseases, particularly the leafhoppers, which currently attack rice in West Sumatra. The National Nuclear Energy Agency (BATAN) is one of the institutions that produce new rice varieties through mutation technology, one of the varieties produced in the Kahayan variety. Kahayan varieties have several advantages over the previous varieties, namely early age, high productivity, and resistance to certain pests and plant diseases. This activity aims to disseminate the breeding of Kahayan rice seeds to breeding farmer groups so that they can fulfill their needs for rice seeds independently. The activity was carried out at the Air Sarasah Farmer Group in Nagari Sungai Batang, Tanjung Raya District, Agam Regency, from November 2019 to March 2020. The activity consisted of disseminating breeding activities, implementing Kahayan rice breeding, and assisting Kahayan rice varieties' breeding. From this activity, farmer groups have been able to better breed rice, according to the operational standards for seed breeding set by the Ministry of Agriculture of the Republic of Indonesia. Also, farmer groups have been able to increase their knowledge of certifying rice seeds. From the results of rice seed breeding, it was obtained that the Kahayan rice seed class Basic Seed (BD) yield was 6.1 tonnes/hectare, which exceeded the national average rice yield, namely in 2018, it was 5.2 tonnes/hectare.